Avaliação em educação física escolar: em busca de aproximações a uma avaliação formativa - Duarte, Larissa Ramos (2018)
The theme of this research covers the assessment of and to learning in the Physical Education curriculum component, in Basic Education - elementary school - which has a formative assessment as a theoretical framework. It looks forward contributing to a critical vision in the extension of the studies on this subject. The aim of this study is to analyze the conceptions and practices of Physical Education teachers assessment of and to learning who participate/participated in the Teachers Professional Development Group - Laboratório de Estudos sobre Escola, Currículo e Edicação Física (Lecef), having as analysis reference the fundamentals of formative assessment. This study is predominantly qualitative and it aims to understand a social phenomenon that is not shown for its measurement or quantitative particularity. It is a research with a descriptive, interpretive and reflective character, because it goes beyond simply describing data, it seeks to discuss and reflect about it, using as theoretical reference Fernandes (2006, 2009), Villas Boas (2007, 2011), and others authors who writes in a formative assessment perspective. The research had two phases, bibliographic and field research. In the bibliographic part we collected related data to our object of study - school physical education assessment - that was used as a theoretical frame to which we supported for the dialogue with the researched reality. The field research had a documentary analysis, which consisted of the analysis of teachers planning documents, called "Teaching Strategies", official documents, observation and interviews. Taught to students in elementary school and they participate/participated in the teachers professional development group (Lecef). The four teachers were observed from February to June in 2017. One of the teachers worked with first grade students and the other three taught to second grade students. The data reveals that teachers evaluation practice, in general, are distant from traditional practices, and they are moving to the principles of a formative assessment. The main limitations of the teachers practice were the lack of systematic records and deep feedbacks.